Population-based versus hospital-based controls: are they comparable? Controles poblaciones frente a controles hospitalarios: ¿son comparables? - Alberto Ruano-Ravina; Mónica Pérez-Ríos; Juan Miguel Barros-Dios (Elsevier, 2008)
Objective: To compare whether there are differences among hospital and population controls. Methods: Two case-control studies were conducted on lung cancer risk factors in the Santiago de Compostela Public Health District. Whereas one used randomly chosen census-based population controls, the other used consecutive hospital controls that went to the reference hospital for non-smoking-related trivial interventions. The differences were analyzed using logistic regression. The dependent variable was type of control (hospital or population). Results: Hospital controls had a similar tobacco habit than population controls, but consumed more alcohol. For those consuming more than 50 ml daily, the risk of being a hospital control was 4.83 (95%CI: 2.55-9.14). Conclusions: There may be some differences between hospital and population-based controls, which must be taken into account in the design of case-control studies. It is necessary to ascertain whether such differences are reproduced at other geographic locations and whether they can affect estimation of exposure-disease. Objetivo: Comparar si hay diferencias entre los controles poblacionales y los hospitalarios. Métodos: Se llevaron a cabo dos estudios de casos y controles sobre factores de riesgo de cáncer de pulmón en el Área Sanitaria de Santiago de Compostela. En uno de los estudios los controles fueron seleccionados aleatoriamente entre la población general, y en el otro los controles hospitalarios fueron incluidos de manera consecutiva entre los individuos que acudían al hospital por intervenciones quirúrgicas banales no relacionadas con el consumo de tabaco. Las diferencias fueron analizadas mediante regresión logística. La variable dependiente fue el tipo de control (hospitalario o poblacional). Resultados: Los controles hospitalarios y los poblacionales tenían un hábito tabáquico similar, pero los controles hospitalarios consumían más alcohol. Para los que consumían más de 50 ml al día, el riesgo de ser un control hospitalario fue de 4,83 (intervalo de confianza del 95%: 2,55-9,14). Conclusiones: Podría haber algunas diferencias entre los controles poblacionales y los hospitalarios que deberían tenerse en cuenta cuando se diseñe un estudio de casos y controles. Es necesario saber si esas diferencias son similares en otras áreas geográficas y si podrían afectar a la estimación de las medidas de efecto entre exposición y enfermedad.